ACELULAR 3D PRINTING IN BONE DEFECT SURGICAL RECONSTRUCTION - Micic, Milutin; Djuric, Marija (Medicinski podmladak, 2023)
3D printing in medicine represents one of the fastest-growing fields, which has awakened the highest expectations in biomedicine. 3D printing is predominantly used when replacing autografts and xenografts with alloplastic personalized tissue substitutes and constructs. This publication will present an overview of contemporary literature dealing with acellular 3D printing in reconstructing bone defects. It will also describe the 3D printing technology, the scope and the main problems it faces in reconstructing bone defects. This review will include the application of 3D printing technology in preoperative surgical planning, the creation of personalized medical models and surgical guides, as well as acellular 3D printing in bone tissue engineering, i.e. in the production of bone scaffolds. We will briefly refer to the application of 3D printing in our country because the available literature indicates a contrast between the current needs and the use of this technology in reconstructive skeletal surgery in Serbia. The neglected and unused benefits of modern 3D printing methods burden the health system with significant socio-economic consequences for public health.